Artisans' Cast Stone and Ironwork (1925)
Artisan's cast stone and ironwork on Elephant Hill. Elephant Hill was the nickname for the area east of the garages-so called because Marianne, the elephant, lived there. The dude wrangler's stables are visible at the right. The lions were used for the lamp standards on the bell towers.